Likelihood of Myocardial Infarction during Stroke Rehabilitation Preceded by Cardiovascular Screening and an Exercise Tolerance Test: The Locomotor Experience Applied Post-Stroke (LEAPS) Trial. Issue 8 (December 2014) - Nadeau, Stephen E.; Rose, Dorian Kay; Dobkin, Bruce; Wu, Samuel S.; Dai, Yufeng E.; Schofield, Richard; Duncan, Pamela W.; ,
Background: Coronary artery disease is highly prevalent in patients with stroke, but because revascularization does not improve major clinical outcomes in patients with stable coronary artery disease relative to intensive medical therapy, routine evaluation for this disease is not warranted in stroke patients. However, it might be warranted in patients destined to undergo vigorous physical therapy. The Locomotor Experience Applied Post-Stroke study, a randomized controlled trial of 408 participants that tested the relative efficacy of two rehabilitation techniques on functional walking level, provided the opportunity to address this question. Aim: The study aims to test the efficacy of screening for cardiovascular disease and an exercise tolerance test in assuring safety among patients undergoing vigorous rehabilitation for gait impairment. Methods: All participants were screened for serious cardiovascular and pulmonary conditions. At six-weeks poststroke, they also completed a cardiovascular screening inventory and underwent an exercise tolerance test involving bicycle ergometry. Participants received 36, 90-min sessions of a prescribed physical therapy (three per week), initiated at either two-months or six-months poststroke. Results: Twenty-nine participants were excluded on the basis of the cardiac screening questionnaire, and 15 failed the exercise tolerance test for cardiovascular reasons. No participant experienced a cardiac event during a treatment session. Two participants experienced myocardial infarctions, but continued in the trial. In three additional participants, myocardial infarctions caused or contributed to death. Conclusions: The combination of a negative cardiac screen and the absence of exercise tolerance test failure appeared to have a high negative predictive value for cardiac events during treatment, despite the likelihood of a high prevalence of coronary artery disease in our population.